2014
DOI: 10.1002/stem.1747
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the NR4A Orphan Nuclear Receptor NOR1 in Hematopoietic Stem Cells Accelerates Atherosclerosis

Abstract: Objective The NR4A orphan nuclear receptor NOR1 functions as a constitutively active transcription factor regulating cellular inflammation and proliferation. In the present study, we employed bone marrow transplantation to determine the selective contribution of NOR1 expression in hematopoietic stem cells to the development of atherosclerosis. Methods and Results Reconstitution of lethally irradiated apoE−/− mice with NOR1-deficient hematopoietic stem cells accelerated atherosclerosis formation and macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 46 publications
(82 reference statements)
2
34
0
Order By: Relevance
“…Moreover, macrophage NOR1 seems to play a protective role in atherogenesis, since it inhibits the inflammatory response of macrophages as well as their ability to transform into foam-cells [15]. In line with this observation, NOR1 deletion in hematopoietic cells accelerates atherosclerosis progression by increasing macrophage infiltration and proliferation in atherosclerotic lesions [21]. Moreover, expression of NOR1 has been recently described in murine mast cells, where it controls the cell response to allergens [22].…”
Section: Introductionmentioning
confidence: 78%
“…Moreover, macrophage NOR1 seems to play a protective role in atherogenesis, since it inhibits the inflammatory response of macrophages as well as their ability to transform into foam-cells [15]. In line with this observation, NOR1 deletion in hematopoietic cells accelerates atherosclerosis progression by increasing macrophage infiltration and proliferation in atherosclerotic lesions [21]. Moreover, expression of NOR1 has been recently described in murine mast cells, where it controls the cell response to allergens [22].…”
Section: Introductionmentioning
confidence: 78%
“…Furthermore, another study of vascular smooth muscle cells also indicated a different result . However, other NR4A3 studies have obtained different results as well, such as Qing H et al, who reported that haematopoietic cell‐specific NR4A3 knockout (KO) accelerates atherosclerosis with monocytosis, while full NR4A3 KO mice showed decreased atherosclerosis according to another study, suggesting that NR4A3 possesses cell‐specific function.…”
Section: Discussionmentioning
confidence: 97%
“…The first study on NR4A3 focused on neurons; NR4A3‐deficient mice showed defects in their inner ear development . Study of its function in atherosclerosis showed that haematopoietic cell–specific NR4A3 knockout induced atherosclerosis . Other researchers also identified that NR4A3 is involved in vascular remodelling and arterial disease .…”
Section: Introductionmentioning
confidence: 99%
“…Nr4a3 has been shown to play an important role in cell survival and proliferation in nonhematopoietic cells (20,21). Nr4a3 expression in monocytes is probably antiatherogenic (22). In lymphocytes, Nr4a3 is involved in the negative selection of T cells, together with Nr4a1 (23).…”
Section: Cd11bmentioning
confidence: 99%